2015
DOI: 10.1530/rep-15-0252
|View full text |Cite
|
Sign up to set email alerts
|

Uterine and placental KISS1 regulate pregnancy: what we know and the challenges that lie ahead

Abstract: Hypothalamic KISS1 and its derivatives (kisspeptins) are now well recognized as potent stimulators of GnRH secretion and thereby major regulators of the neuroendocrine-reproductive axis. Recent studies in the mouse strongly suggest that independent of the hypothalamus and pituitary, peripherally derived KISS1 also regulates fertility, and disruption of local KISS1 signaling in the ovary and uterus is sufficient to trigger infertility. With this increasing recognition that peripherally derived KISS1 regulates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Human placentation is an intricate process of fetal-maternal interaction that shares some similarities with cancer migration and metastasis (35). In this context, kisspeptins, initially identified as potential metastasis-suppressing factors abundantly expressed in the placenta, were suspected as important players for the fine control of trophoblast invasion and placentation (17,18). This placental dimension of kisspeptins was further attested by the proven elevation of kisspeptin levels already at early stages of human gestation (21).…”
Section: Circulating Kisspeptin/mir-324-3p As New Early Biomarker Of Epmentioning
confidence: 99%
See 3 more Smart Citations
“…Human placentation is an intricate process of fetal-maternal interaction that shares some similarities with cancer migration and metastasis (35). In this context, kisspeptins, initially identified as potential metastasis-suppressing factors abundantly expressed in the placenta, were suspected as important players for the fine control of trophoblast invasion and placentation (17,18). This placental dimension of kisspeptins was further attested by the proven elevation of kisspeptin levels already at early stages of human gestation (21).…”
Section: Circulating Kisspeptin/mir-324-3p As New Early Biomarker Of Epmentioning
confidence: 99%
“…In our study, the observed drop in KISS1 expression might have an impact on the whole process of trophoblast invasion, which is inhibited by locally produced kisspeptins (20,37), and might facilitate nidation at an ectopic site. Interestingly, Kisspeptin and miR-324-3p in Ectopic Pregnancy kisspeptins have been suggested also to facilitate initial embryo adhesion/implantation at proper endometrial sites (18,38), while high tubal expression of Kiss1/kisspeptin has been proposed as mechanism to prevent ectopic implantation in rats (39). Whether early deregulation of kisspeptin production might facilitate adherence at extra-uterine sites in human pregnancy is yet to be elucidated.…”
Section: Circulating Kisspeptin/mir-324-3p As New Early Biomarker Of Epmentioning
confidence: 99%
See 2 more Smart Citations
“…15 It is most likely that the increase in the total number of trophoblast cells throughout the course of gestation is responsible for the dramatic increase in serum kisspeptin levels. 16 Kisspeptin are mainly derived from placenta, the levels of plasma or serum kisspeptin can probably act as a biomarker for the function of the placenta and therefore viability of pregnancy. [17][18][19] Dhillo et al, showed that Circulating kisspeptin levels fell again 5 days post-delivery to comparable concentrations prior to pregnancy, implicating a placental source.…”
Section: Discussionmentioning
confidence: 99%